Imovation in shaping dynamic capabilities of organisations - Krzakiewicz Kazimierz; Cyfert Szymon (Management)
The underlying assumption of the article is that imitation is as important as innovation when creating a long-term competitive advantage, and that a systematic, strategic approach to imitation is necessary to ensure efficient and effective innovation. Viewed in this light, imitation is a rare and complex dynamic capability which organisations should properly develop and skillfully use. Imitators provide customers with products that are both better and cheaper. This article contributes to a discussion of innovative processes and their role in shaping dynamic capabilities of organisations. It attempts to portray the essence and nature of imitation and identifies benefits which copying what other organisations do can bring in terms of dynamic capabilities.